The correlations among undergraduate EFL students’ reading habit, multiple intelligences, and writing mastery - Lestari, Ayu; Lazy, Sofendi; Petrus, Ismail (Universitas Pendidikan Indonesia, 2018)
This study aims to investigate the correlations among undergraduate EFL students’ reading habit, multiple intelligences, and their writing mastery. It also aims to identify types of reading habit and multiple intelligences that mostly influence students’ writing mastery. In this correlational study, the data were collected through questionnaires and test. The data were analyzed by using correlation and linear regression analyses. The results show that there are no significant correlations between reading habit and writing mastery, between multiple intelligences and writing mastery, and between predictor variables and criterion variable.